2017
DOI: 10.1111/arcm.12266
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic and Geochemical Investigations on the Pottery Production from Arslantepe–Malatya (Eastern Anatolia) from the Fourth to the Second Millennium BCE: Technological Continuity, Innovation and Cultural Change

Abstract: The petrographic and geochemical analyses of 130 Late Chalcolithic 3 (LC3, 3800 bce) to Early Bronze Age IIIB (EBAIIIB, 2000 bce) ceramics from Arslantepe and the Malatya Plain in the Eastern Anatolian Upper Euphrates have identified critical differences in raw material procurement and paste preparation, reflecting typological, chronological and cultural changes. Based on these differences, distinct modes of production that correspond to phases reflecting significant social, economic and political changes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…CaO, P 2 O 5 ), most of them are instead related to distinct local strategies in raw material procurement and paste preparation. Indeed, previous studies have already demonstrated that the geochemical variation in the ceramics from Arslantepe is mostly linked to the exploitation of more and less calcareous clay deposits tempered with materials characterized by different mafic/felsic/alkaline affinities [ 85 ]. Calcareous and non-calcareous deposits are respectively available in the plain and in the southern Anti-Taurus Mountains.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CaO, P 2 O 5 ), most of them are instead related to distinct local strategies in raw material procurement and paste preparation. Indeed, previous studies have already demonstrated that the geochemical variation in the ceramics from Arslantepe is mostly linked to the exploitation of more and less calcareous clay deposits tempered with materials characterized by different mafic/felsic/alkaline affinities [ 85 ]. Calcareous and non-calcareous deposits are respectively available in the plain and in the southern Anti-Taurus Mountains.…”
Section: Resultsmentioning
confidence: 99%
“…Since the paper aims at assessing the uniformity of the local production modes, vessels of underrepresented foreign typology (e.g. the rare beveled rim bowls found at the site) or not matching geochemically and petrographically with local reference fields have been excluded [ 74 , 84 , 85 ]. The petrographic data used in this paper refer to 167 thin sections (Tables 2 and 3 ; Fig 6 ) that are grouped according to: 1) calcareous versus non-calcareous clay matrix; 2) the presence/absence of organic temper; 3) the geological origin of mineral and rock inclusions, which may refer to variegated volcanic, plutonic and metamorphic environments.…”
Section: Sampling Strategy and Methodsmentioning
confidence: 99%
See 3 more Smart Citations